Connection between gut microbiota and Anorexia Nervosa. Literature review - Polańska, Paulina; Sokołowska, Katarzyna; Kulak, Maria; Moreau, Igor; Bereza, Dawid; Lang, Miriam; Woch, Barbara (Journal of Education, Health and Sport, 2024)
Introduction: Anorexia Nervosa (AN) stands as a severe mental disorder characterized by the highest mortality rate within the realm of psychiatric conditions. Its etiology encompasses genetic, neurobiological, environmental, and developmental factors. Recent investigations have shed light on the potential impact of the gut microbiota on the genesis and progression of AN. Aim of the Study: The aim of this paper is to provide a comprehensive review of the existing findings on relationship between gut dysbiosis and AN. The intention is to present new perspectives that contribute to a more detailed understanding of the multifaceted nature of this serious disorder. Description of the State of Knowledge: The gut microbiota takes a central role in modulating various physiological processes. Dysbiosis, which refers to an imbalance in gut microbiota composition, has recently drawn attention because of its association with several mental disorders. In the context of AN, studies have shown reduced microbial diversity and notable changes in specific bacterial populations. The influence of the gut microbiota on AN includes disturbances in the digestive system, changes in eating behaviours, and associations with related conditions such as anxiety and depression. Mechanisms such as the gut-brain axis, hormonal regulation and molecular mimicry contribute to these associations. Conclusions: Recognition of the pivotal role played by the gut microbiota in AN opens up avenues for potential therapeutic interventions. Pro- and prebiotics, along with fecal transplantation, emerge as promising modalities in the treatment of AN. Ongoing research is essential to further elucidate this evolving field, ultimately facilitating the development of targeted interventions for individuals with AN.